Closed Incision Negative Pressure Wound Therapy in Vascular Surgery: A Systematic Review and Meta-Analysis. (September 2019) - Wee, Ian J.Y.; Syn, Nicholas; Choong, Andrew M.T.L.
Abstract : Background: Closed incision negative pressure wound therapy (CiNPT) may be a valuable treatment option for surgical site infections. This systematic review and meta-analysis sought to compare CiNPT against conventional wound care after vascular procedures. Methods: This study conformed to the PRISMA guidelines. An electronic search was performed on Medline/Pubmed, EMBASE, and the Cochrane Library. The date of last search was July 11 2018. Relative risks and mean differences for primary and secondary outcomes were calculated. A random effects model was used for substantial heterogeneity ( I 2  > 30%). The Cochrane Risk of Bias tool was employed to rate the methodological quality of the included studies, whilst the GRADE approach was use to grade the level of evidence for the observed effects. Results: Of 47 studies, five randomised controlled trials (RCTs) were included, comprising 662 patients, of which 47.9% underwent CiNPT and 52.1% received conventional care. The overall risk of infection (RR = 0.31, 95% CI 0.21–0.47) (high quality), Szilagyi Grades I (RR = 0.35, 95% CI 0.20–0.60) (high quality), and III (RR = 0.17, 95% CI 0.04–0.68) (high quality) infections, need for antibiotics (RR = 0.36, 95% CI 0.20–.64) (high quality), and surgical re-intervention (RR = 0.27, 95% CI 0.27–0.98) (high quality) were lower in the CiNPT group. However, there were no significant differences in the risk of Grade II (RR = 0.59, 95% CI 0.10–3.66) (moderate quality), as well as length of hospital stay (mean difference, MD = −0.59, 95% CI –2.48 to 1.31) (moderate quality), and 30 day mortality (RR = 3.95, 95% CI 0.17–94.76) (high quality). Conclusion: While there is evidence demonstrating that CiNPT reduces the risk of Grades I and III infections and re-interventions, there was a noticeable lack of difference in other important post-operative outcomes. Further well designed RCTs are needed to corroborate these findings.